Fear of Evaluation and Communication Apprehension: The Mediating Role of Social Skills Deficits - Karna, Wioleta; Binti Zulkifli, Nur Aisyah (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective: This study aimed to examine the mediating role of social skills deficits in the relationship between fear of evaluation and communication apprehension among university students in Malaysia. Methods and Materials: A descriptive correlational design was employed, involving a sample of 405 undergraduate students selected using the Krejcie and Morgan sampling table. Participants were assessed using three standardized instruments: the Fear of Negative Evaluation Scale (FNE), the Social Skills Inventory (SSI), and the Personal Report of Communication Apprehension (PRCA-24). Data analysis included Pearson correlation using SPSS-27 and Structural Equation Modeling (SEM) using AMOS-21 to evaluate direct, indirect, and total effects among the variables. Model fit was assessed using standard indices, including CFI, TLI, RMSEA, and χ²/df. Findings: Fear of evaluation was positively correlated with both social skills deficits (r = .48, p < .001) and communication apprehension (r = .62, p < .001), while social skills deficits were also positively associated with communication apprehension (r = .55, p < .001). SEM analysis revealed a significant direct effect of fear of evaluation on communication apprehension (β = 0.39, p < .001) and a significant indirect effect mediated by social skills deficits (β = 0.20, p < .001), resulting in a substantial total effect (β = 0.59, p < .001). The model demonstrated excellent fit (CFI = 0.96, RMSEA = 0.045, χ²/df = 1.98). Conclusion: The findings underscore the critical role of social skills deficits in amplifying the effects of fear of evaluation on communication apprehension. Interventions targeting both evaluative fears and interpersonal competence are essential to mitigating communicative anxiety in educational settings